Comparative efficacy of gait training for balance outcomes in patients with stroke: A systematic review and network meta-analysis - Lyu, Tianyi; Yan, Kang; Lyu, Jiaxuan; Zhao, Xirui; Wang, Ruoshui; Zhang, Chaoyang; Liu, Meng; Xiong, Chao; Liu, Chengjiang; Wei, Yulong (Frontiers in Neurology, 2023)
Abstract Background: Growing evidence suggested that gait training could improve the balance outcomes of stroke patients. However, it remains unclear which type of gait training is more effective in improving certain types of balance outcomes in patients with stroke. Thus, this network meta-analysis included six types of gait training (treadmill:TT, body-weight-supported treadmill:BWS-TT, virtual-reality training:VR, robotic-assisted gait training:RA-GT, overground walking training:OWT and conventional gait training:CGT) and four types of balance outcomes (static steady-state balance:sSSB, dynamic steady-state balance:dSSB, proactive balance:PB, balance test batteries:TB), aiming to compare the efficacy of different gait training on specific types of balance outcomes in stroke patients and determine the most effective gait training. Method: We searched PubMed, Embase, Medline, Web of Science and Cochrane Library databases from inception until April 25, 2022. Randomized controlled trials of gait training for the treatment of balance outcomes after stroke were included. RoB2 was used to assess risk of bias in the included studies. Frequentist random-effects network meta-analysis was used to evaluate the effect of gait training on four categories of balance outcomes. Result: 61 RCTs from 2551 citations, encompassing 2328 stroke patients, were included in this study. Pooled results showed that BWS-TT(SMD=0.30, 95% CI [0.01, 0.58]) and TT(SMD=0.25, 95% CI [0.00, 0.49]) could improve the dSSB. VR(SMD=0.41, 95% CI [0.10, 0.71]) and BWS-TT(SMD=0.41, 95% CI [0.02, 0.80]) demonstrated better effects in improving TB . However, none of included gait training showed significant effect on sSSB and PB. Conclusion: Gait training is an effective therapy in improving dSSB and TB of stroke patients. However, gait training had no significant effect on sSSB and PB performance. To achieve maximum efficacy, clinicians should consider this evidence when recommending rehabilitation training to stroke patients. Considering BWS-TT is not common for chronic stroke patients in clinical practice, TT is recommended for those who want to improve dSSB, and VR is recommended for those who want to improve TB. Limitation: Missing evidence in relation to some types of the gait training is supposed to be taken into consideration. Moreover, we fail to assess RB in this NMA since few included trials reported this outcome.